2022
DOI: 10.1186/s40643-022-00576-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pH-responsive high molecular-weight chitosan/poly (vinyl alcohol) hydrogel prepared by gamma irradiation for localizing drug release

Abstract: AbstractpH-sensitive hydrogels prepared by gamma irradiation find promising biological applications, partially, in the field of localized drug liberation. Herein, optimal conditions for fabricating high-molecular-weight chitosan/polyvinyl alcohol hybrid hydrogels using gamma irradiation at 10, 25, and 30 kGy were investigated by studying the water uptake behavior, the pore size on the surface, and thermal stability. Furthermore, the crosslinking mechanism of irradiated hydrogels was examined via solid-state 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The Higuchi equation is possibly the first model that quantifies drug release from thin films. Due to its simplicity [ 14 ], the Higuchi equation is widely used to correlate the kinetic of drugs released from various solid systems [ 8 , 15 , 16 , 17 , 18 , 19 , 20 ]. Th Higuchi equation has the following for: where n t is the cumulative amount of the drug released at time t , while n max is the maximum amount of drug that can be released at an infinite time.…”
Section: Resultsmentioning
confidence: 99%
“…The Higuchi equation is possibly the first model that quantifies drug release from thin films. Due to its simplicity [ 14 ], the Higuchi equation is widely used to correlate the kinetic of drugs released from various solid systems [ 8 , 15 , 16 , 17 , 18 , 19 , 20 ]. Th Higuchi equation has the following for: where n t is the cumulative amount of the drug released at time t , while n max is the maximum amount of drug that can be released at an infinite time.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that drugloaded AM-O-β-CD showed a pH dependent drug release pro le. The drug release from the nanostructure in low pH was much higher due to Schiff base, high drug loading capacity and increase drug solubility [34] than the pure drug in the same environment.…”
Section: Characterization Of Drug Loaded Am-o-β-cd Nanoparticlementioning
confidence: 97%
“…The nanobeads composed of chitosan and agarose exhibit pH-sensitive releases of drugs, with different drug releases in tumor-simulated and normal cell-simulated buffers. Tran Vo et al [ 166 ] crosslinked chitosan/PVA hydrogels by using gamma irradiation. The higher swelling ratio of hydrogels was observed under acidic conditions, due to the protonation of amino groups.…”
Section: Pharmaceutical and Biomedical Applications Of Chitosan-based...mentioning
confidence: 99%